Optimalisasi Limbah Batang Pisang Kepok untuk Pemberdayaan Perempuan dan Peningkatan Kesejahteraan Masyarakat di Desa Tadenas, Pulau Moti, Maluku Utara - Mila Fatmawati; Nursamsi Nursamsi; Hamidin Rasulu; Nurjanna Albaar; Herman Darwis (Universitas Khairun, 2025)
The utilization of kepok banana stem waste is still not optimal in Tadenas Village, Moti Island, North Maluku. So far, banana stems are only considered as worthless agricultural leftovers. The main problem faced by the community, especially women, is the limited knowledge in processing local waste into innovative products that can be marketed. This activity aims to empower women through optimizing kepok banana stem waste into innovative jerky products with the